HUBUNGAN PEKERJAAN, STATUS EKONOMI, PENDIDIKAN IBU HAMIL DENGANPENGETAHUAN IMUNISASI TETANUS TOKSOID DI PUSKESMAS BATURRADEN II KECAMATAN BATURRADEN KABUPATEN BANYUMAS TAHUN 2014 - Prihastanti, Erma; Hastuti, Puji (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Based on experiment analytical report arranged by WHO that tetanus was still getting the cause of mortality and maternal, neonatal pain in Indonesia in 2000-2010. There were 137 per 100.000 childbirth who have got death because of tetanus. In 2010 it was reported that 147 cases with 84 were dead. In 2012 there were 495 the pregnant who had TT immunization were only 307 the pregnant (60, 2%) at Baturaden II social center clinic service.This research is analytical observation located at Baturaden II social center clinic service in April 2014. The number of sample is 60 the pregnant which using random techniques. The used instrument of research is closing questionnaires meanwhile for analytical data used unvaried and bivariate analysis. There are correlation between job to mother knowledge about TT immunization at Baturaden II social center clinic service at Baturaden subdistrict at Banyumas regency in 2014 with correlation coefficient of chi square X2 count is 8,085 and 0,018 of p-value;   there are correlation between economic statuses to mother knowledge about toxoids tetanus (TT) immunization at Baturaden II social center clinic service at Baturaden subdistrict at Banyumas regency in 2014 with correlation coefficient of chi square X2 count is 14,447 and 0,001 of p-value;  there are correlation between education to mother knowledge about toxoids tetanus (TT) immunization at Baturaden II social center clinic service at Baturaden subdistrict at Banyumas regency in 2014 with correlation coefficient of chi square X2 count is 25,031 and 0,0008 of p-value. The pregnant are expected to be more active participating counseling   immunization of TTto increase knowledge of TT immunization through electronica or paper media. Key Words: Job, Economic Statuses, Education, Immunization of TT Knowledge.